2021
DOI: 10.1200/go.20.00573
|View full text |Cite
|
Sign up to set email alerts
|

Retrospective Analysis of Presentation, Treatment, and Outcomes of Multiple Myeloma at a Large Public Referral Hospital in Eldoret, Kenya

Abstract: PURPOSE Treatment patterns and survival outcomes of patients with multiple myeloma (MM) in Kenya have not been adequately characterized. The objectives of this study were to describe the clinical, laboratory, and imaging findings at diagnosis, to describe the treatment offered, and to determine the survival outcomes of patients with MM over an 11-year period. PATIENTS AND METHODS A retrospective chart review was carried out for all patients who were diagnosed and treated for MM at Moi Teaching and Referral Hos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 24 publications
5
3
0
Order By: Relevance
“…Our findings from the demographic variables in this study were similar to those from previous MM studies carried out in Sub-Saharan Africa that have reported a male predominance and median age at presentation of between 53 to 62 years (5,6,(40)(41)(42). This is a younger age at diagnosis than described in studies conducted in predominantly Caucasian populations such as that by Kyle et al and Kristinsson et al who reported a median age of 66 and 70 years, respectively, (43,44).…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Our findings from the demographic variables in this study were similar to those from previous MM studies carried out in Sub-Saharan Africa that have reported a male predominance and median age at presentation of between 53 to 62 years (5,6,(40)(41)(42). This is a younger age at diagnosis than described in studies conducted in predominantly Caucasian populations such as that by Kyle et al and Kristinsson et al who reported a median age of 66 and 70 years, respectively, (43,44).…”
Section: Discussionsupporting
confidence: 90%
“…This heterogeneity has been observed among different racial groups. The incidence of MM and Monoclonal Gammopathy of Undetermined Significance (MGUS) is two-to three-fold higher with an earlier age of onset of the disease in those of African descent compared to Caucasians (4)(5)(6). United States-based population studies have also indicated a greater overall survival (OS) and disease specific survival (DSS) in patients of African descent when compared to European Americans, suggesting more indolent disease (4,7).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our findings showed that male practitioners were five times more likely to be aware of the MM than females, and this could be because males (61%) made up the majority of the GPs compared to 39% of females, of which GPs are the most common practitioners patients initially consult. 17 , 36 , 37 Our finding also found that participants with six or more years post-medical degrees were aware of MM, which shows that most of the respondents in our study were experienced.…”
Section: Discussionsupporting
confidence: 73%
“… 5 Conversely, a modest OS of 29 months was recorded among patients with ndMM receiving treatment in a tertiary hospital in Kenya between 2009 and 2019 where SCT was not available. 6 Late diagnosis which was hypothesized to be a major contributor to the dismal survival observed in Kenya may be attributed, to a large extent, to inadequate skills among primary care teams in Kenya to identify potential patients with myeloma and refer them for specialized care. 7 Innovations that bridge the skills gap between primary health care teams and experts at tertiary centers are therefore desperately needed.…”
Section: Introductionmentioning
confidence: 99%